KAJIAN BIO-TEKNIK PEMANFAATAN SUMBERDAYA IKAN TENGGIRI DAN DISTRIBUSI PEMASARANNYA DI KABUPATEN BANGKA - Moch. Prihatna Sobari; Arief Febrianto (Jurnal Teknologi Perikanan dan Kelautan, 2010)
This study aims to identify up to, local, seasonal fishing, fishing equipment productivity tenggiri, marketing of the catch and determine patterns of utilization of resources yellow tail fish in a sustainable Kabupaten Bangka. Research method used was the descriptive survey method of case study (case study) and the sampling is done purposively. Data analysis includes the analysis and bio-engineering techniques. Analysis of bio-engineering approach using model CYP. Tenggiri fish in the waters of Bangka Regency arrested with using gillnet catch and pacing overextend. Gill nets in Kabupaten Bangka included in jaringi gill away (drift gillnet) and his fishing nets with the net tenggiri term. Kontruksi catching equipment consists of selambar ropes, nets, rope and buoy up ris. Overextend rod for fishing tenggiri have construction that consists of the Reel (rooler), swivel (swivel), string (line), ballast (sinker) and the rod (hook). Fishing season in the month at The Bangka-month fishing season which occurs on the March, May and June and August and October with the IMP more than 100%. Regional utilization of fishing ground catching fish tenggiri at The Regency Bangka is catching on line 1 (in the coastal waters of up to 6 miles). Utilization of fish resources in sustainable tenggiri can be done with the regime to know the management of fish resources optimally tenggiri where the alleged biological biological overfishing has occurred with the actual effort is 798 more than the trip management of fish resources optimally tenggiri trip of 379. Tenggiri local marketing of fish is done by traders and merchants and retailers sold to consumers, while the export is done by marketing companies. Selling price, marketing margins and profits earned with the short channel with Fisherman share the same akan provide for share traders and the larger fishing companies